A novel somatic PLCG2 variant associated with resistance to BTK and SYK inhibition in chronic lymphocytic leukemia. (2nd November 2020) - Raghunathan, Vikram; Fan, Guang; Kittai, Adam S.; Okada, Craig; Danilov, Alexey V.; Spurgeon, Stephen E.
Abstract: The treatment of chronic lymphocytic leukemia (CLL) has been transformed by the use of targeted small molecules inhibiting components of the B cell receptor (BCR) signaling pathway ( Haematologica, 103, 2018 and e204; Curr Hematol Malig Rep, 14, 2019, 302). Chief among these is ibrutinib, an irreversible inhibitor of Bruton tyrosine kinase (BTK), which produces deep, durable responses in CLL with good tolerability ( Haematologica, 103, 2018 and e204). Though prolonged exposure to the drug can exert selective pressure on CLL cells and allow for the emergence of drug‐resistant clones, primary ibrutinib treatment failure is rare ( Expert Rev Hematol, 11 and 2018, 185; N Engl J Med, 370, 2014 and 2352; N Engl J Med, 373, 2015 and 25, 2425; Blood, 128, 2016 and 2199). Activating mutations in the gene PLCG2, which encodes a downstream target of BTK, appear to enable constitutive BCR signaling and have been associated with ibrutinib resistance ( Int J Cancer, 146 and 2020, 85; J Clin Oncol, 35, 2017 and 1437; Blood, 126, 2015 and 61). In recent years, novel investigational agents have targeted other components of the BCR pathway. Among these is entospletinib, an orally bioavailable, selective inhibitor of splenic tyrosine kinase (SYK) ( Blood, 126, 2015 and 1744), which lies upstream of the enzyme phospholipase C‐gamma‐2 (PLCG2). Here, we describe a patient who was found to harbor a novel somatic variant of PLCG2 and experienced a lack of treatment response to both ibrutinib and entospletinib.